2020
DOI: 10.1186/s12891-020-03774-5
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable pins for lateral condylar fracture of the humerus with an early delayed presentation in children: a retrospective study of biodegradable pin vs. Kirschner wire

Abstract: Background The clinical outcome of open reduction and internal fixation (ORIF) for delayed lateral condylar fracture of the humerus (LCFH) varies in different studies, but ORIF for LCFH with an early-delayed presentation usually resulted in significant improvement of elbow function. Early delayed presentation is defined as a period of 3 to 12 weeks from the injury. This study aims to compare the clinical outcomes of biodegradable pin (BP) vs. Kirschner wire (KW) in the treatment of LCFH with an early delayed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…On the other hand, satisfactory outcomes have been reported in other studies [15][16][17], especially in patients with an early-delayed presentation. Li et al [10] retrospectively studied 43 lateral LCFH where 17 of their patients were treated with K-wires and 26 patients were treated with biodegradable pins. The authors hypothesized that open reduction and internal fixation for LCFH with an early-delayed presentation produced satisfactory outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, satisfactory outcomes have been reported in other studies [15][16][17], especially in patients with an early-delayed presentation. Li et al [10] retrospectively studied 43 lateral LCFH where 17 of their patients were treated with K-wires and 26 patients were treated with biodegradable pins. The authors hypothesized that open reduction and internal fixation for LCFH with an early-delayed presentation produced satisfactory outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of early versus delayed treatment has been a topic of interest for various fracture types [6][7][8][9]. It is possible that early operative treatment for LCFH may prevent complications such as infection, malunion and nonunion [10]. However, few studies in the literature comparing early and delayed surgery for displaced fractures of the lateral condyle of the humerus have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, in recent years, this class of resorbable fixation materials has aroused considerable interest in maxillofacial surgery [ 40 , 46 ]. Other advantages include anti-inflammatory [ 47 , 48 ] and antibacterial activity [ 49 , 50 , 51 ] as well as bone formation induction [ 52 , 53 ]. However, primacy leads to the fact that this fixation material will not have to be removed from the body through a second surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of preschool children with unossified secondary ossification center is seen to be normal-like on the X-ray images, and the large cartilaginous "empty spaces" may harbor harmful injuries, which could cause serious consequences or deformities. [1][2][3] In 2010, Waters et al identified 8 fractures with Radiographic Appearance Seemed Harmless (TRASH) fracture of the elbow, recommending that surgeons should be more careful to do physical examination. [4] The ultrasound or magnetic resonance imaging were also advised to confirm diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of preschool children with unossified secondary ossification center is seen to be normal-like on the X-ray images, and the large cartilaginous “empty spaces” may harbor harmful injuries, which could cause serious consequences or deformities. [ 1 3 ]…”
Section: Introductionmentioning
confidence: 99%